Crustal Structure of the Seismogenic Volume of the 2010–2014 Pollino (Italy) Seismic Sequence From 3D P- and S-Wave Tomographic Images - Napolitano, Ferdinando; Amoroso, Ortensia; La Rocca, Mario; Gervasi, Anna; Gabrielli, Simona; Capuano, Paolo (Frontiers in Earth Science, 2021)
A tomographic analysis of Mt. Pollino area (Italy) has been performed using earthquakes recorded in the area during an intense seismic sequence that occurred between 2010 and 2014. 870 local earthquakes with magnitude ranging from 1.8 to 5.0 were selected considering the number of recording stations, the signal quality and the hypocenter distribution. P- and S-wave arrival times were manually picked and used to compute 3D velocity models through tomographic seismic inversion. The resulting 3D distributions of VP and VS are characterized by high resolution in the central part of the investigated area, and from surface to about 10 km below sea level. The aim of the work is to obtain high-quality tomographic images to correlate with the main lithological units that characterize the study area. The results will be important to enhance the seismic hazard assessment of this complex tectonic region. These images show the ductile Apennines Platform (VP=5.3 km/s) overlaying the brittle Apulian Platform (VP=6.0km/s) at depth of around 5 km. The central sector of the area shows a clear fold and thrust interface. Along this structure most of the seismicity occurred, including the strongest event of the sequence (MW 5.0). High VP (>6.8 km/s) and high VP/VS (>1.9) patterns, intersecting the southern edge of this western seismogenic volume, have been interpreted as water saturated rocks, in agreement with similar geological context in the Apennines. These fluids could have played a role in nucleation and development of the seismic sequence. Recent study revealed the occurrence of clusters of earthquakes with similar waveforms along the same seismogenic volume. The hypocenters of these cluster events have been compared with the events re-located in this work. Jointly, they depict a 10km x 4km fault plane, NW-SE oriented, deepening towards SW with a dip angle of 40-45°. Instead, the volume of seismicity responsible for the ML 4.3 earthquake developed as a mainshock-aftershock sequence, occurring entirely within the average-to-low VP/VS Apennines Platform. Our results agree with other independent geophysical analysis carried out in this area, and they could significantly improve the actual knowledge of the main lithologic units of this complex tectonic area.